Pengaruh Pertumbuhan Ekonomi Terhadap Kemiskinan di Kabupaten Aceh Timur - Safuridar, Safuridar (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2017)
This study aims to determine the effect of economic growth on poverty in East Aceh. The data used in this study is secondary data obtained from the results of direct research both from BPS Kabupaten Aceh Timur and from the website of BPS. The data obtained were analyzed by using simple linear regression equation, coefficient of determination and t test. The result revelead that Y = 166.859 - 0,055X. 166,859 people are the number of poor people in East Aceh which is not influenced by economic growth. Furthermore, the regression coefficient b of -0.055 indicates that the variable of economic growth negatively affect poverty and if economic growth is increased by 1%, it will decrease poverty by 0,055%. Coefficient of determination R2 equal to 0,776 or equal to 77,6%, meaning that the influence of economic growth variable to poverty is 77.6% and the remaining 22.4% is influenced by other variables that are not examined in this study. The hypothesis that the economic growth has negative effect to poverty in East Aceh is acceptable. This is in accordance with the result of regression equation with negative economic growth coefficient is 0,055 and t-table <ttable is -5,263 <1,895. Therefore, it can be concluded that the economic growth have both negative and significant effect to poverty in East Aceh.